P-B01 First Inventory of Access and Quality of Metabolic Surgery across Europe. (16th December 2021) - Sinclair, Piriyah; Vijgen, Guy; Aarts, Edo; Van Nieuwenhove, Yves; Maleckas, Almantas
Abstract: Background: Europe consists of 51 independent countries. Variation in healthcare regulations results in differing challenges faced by patients and professionals. The obesity pandemic has multiple health, economic and social implications. However, metabolic surgery is not universally accessible, with significant variations in its provision. This study aimed to gain insight into compliance with international guidelines; the accessibility and barriers to surgery; patient pathways and qualitor indicators of both metabolic and body contouring surgery after weight loss in different European countries. Methods: This study was initiated during the European Obesity Academy (EOA). Expert representatives in the metabolic field from all 51 European countries were sent a novel, 37-item, electronic self-administered online questionnaire on their data and experiences from the previous year exploring accessibility to and quality indicators for metabolic surgery and body contouring surgery after weight loss. The survey tool was peer-reviewed by experienced researchers and piloted by fifteen experienced researchers with a spread of seniority and specialty. Content and face validity were ensured by peer-review and the piloting process. 45 completed responses were collected.  Results: 68% of countries had eligibility criteria for metabolic surgery; 59% adhered to these. 46% had reimbursement criteria for metabolic surgery. 41% had eligibility criteria for plastic surgery and 31% reimbursement criteria. Average tariffs for a metabolic procedure varied (€800-€ 16000). MDTs were mandated in 78%, with team members varying significantly. Referral practises differed. In 45% metabolic surgery is performed by pure metabolic surgeons. 23% had a metabolic training program. Access to metabolic surgery was rated poor/ very poor in 33%. 35% had a bariatric registry. 24% required a minimum procedure number for metabolic centres; varying from 25 to 200 procedures. Conclusions: This is the first study to describe accessibility and quality data on metabolic and body contouring surgery from most European countries. There are myriad differences between European countries in terms of accessibility to metabolic surgery. Lack of funding, education and structure fuels this disparity. We hope this study will impact standardisation of access and quality indicators for metabolic and body contouring surgery across European countries, as well as be a springboard for further evaluation of international metabolic surgery practices.